Caring for the Older Horse: Common Problems and Solutions - Edward L. Johnson; Kylee Jo Duberstein; Mark Shuffitt (EDIS)
Horses often live into their late 20s and early 30s. But as the horse ages, its needs change, and additional care may be required to keep it as healthy as possible. This 5-page fact sheet addresses changes in the aging horse’s body that impact its requirements, along with possible ways to meet these requirements and solutions to problems that may occur. It was written by Edward L. Johnson, Kylee Jo Duberstein, and Mark Shuffitt, and published by the UF Department of Animal Sciences, October 2010.